PHILOSOPHY AND WESTERN THOUGHT: COMPARATIVE APPROACHES TO EPISTEMOLOGY AND ETHICS - Amie Primarni; Luis Santos; Maria Clara Reyes (Yayasan Adra Karima Hubbi, 2026)
This study explores the comparative approaches to epistemology and ethics within Islamic philosophy and Western thought. Despite centuries of intellectual exchange, the two traditions are often studied in isolation, with minimal attention given to their intersections. Islamic philosophy emphasizes the integration of divine revelation and reason in acquiring knowledge, whereas Western thought traditionally prioritizes empirical evidence and rationalism. In ethics, both traditions share concerns regarding virtue and moral conduct but diverge in their foundations, with Islam grounding ethics in divine will and Western thought emphasizing human reason. The objective of this research is to compare these philosophical traditions, identifying both their points of convergence and divergence in epistemology and ethics. A qualitative research design is employed, focusing on textual analysis of key philosophical works from both traditions, including those of Avicenna, Al-Ghazali, Ibn Rushd, Plato, Aristotle, Kant, and Mill. The findings reveal significant differences in how each tradition understands the nature of knowledge and morality, yet also highlight areas of overlap, particularly in virtue ethics. This study contributes to the broader discourse by promoting a comparative framework for understanding the similarities and differences between Islamic and Western thought. It concludes by emphasizing the potential for cross-traditional dialogue to enrich contemporary philosophical inquiry.